Gambaran Pengetahuan Ibu Balita Umur 1-5 Tahun Tentang Pemberian Tablet Vitamin A Pada Balita Di Puskesmas Pancur Batu Desa Perumnas Simalingkar Tahun 2020 - Merlina Sinabariba; Lindawati Simorangkir (STIKes Santa Elisabeth Medan, 2020)
Background: Long-lasting vitamin A deficiency for toddlers in the body can lead to health problems that lead to an increased risk of pain and death in toddlers. Vitamin A also prevents night vision,Xerophthalmia, corneal damage, and blindness. The purpose of this study was to get an overview of the mother's knowledge about the administration of vitamin A tablets for toddlers. Method: This research is a descriptive with cross-sectional approach. Structured interview involving 58 mothers of toddlers in Puskesmas Pancur Batu. Sampling by quarto sampling. This research was conducted at Puskesmas Pancur Batu Desa Perumnas Simalingkar in 2020. Descriptive data in bivariate analysis to look at sociodemographic relationships, problems in toddlers, and mother’s knowledge of vitamin A tablets for toddlers. Results: The results showed that the mother’s knowledge of toddlers about the administration of vitamin A tablets for toddlers, who are well knowledgeable as many as 44 people (75.9%), knowledgeable enough as many as 13 people (22.4%), and less knowledgeable as 1 person (1.7%) Discussion: It is concluded that there are significant differences in knowledge on the administration of vitamin A for toddlers. The conclusion of this study affects the mother's low-income so that it affects the administration of vitamin A for toddler.